1971
DOI: 10.1083/jcb.50.3.652
|View full text |Cite
|
Sign up to set email alerts
|

Primitive Erythropoiesis in Early Chick Embryogenesis

Abstract: The primitive line of embryonic chick blood cells develop as a relatively homogeneous cohort of cells. Using an analysis based on the continuous uptake of thymidine-3H, we have established the generation time, G1, S, and G2 for progressively more mature generations of these immature erythroblasts. The data indicate that after the initiation of hemoglobin synthesis, the average cell will yield six generations of hemoglobin producing erythroblasts. The older generations of erythroblasts exhibit a longer generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1971
1971
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…We observed that lengths of S and M phases, as well as the length of the G1 phase later, increase after MBT and can be expressed as linear functions of cell cycle time, although in our observations lengths of the G2 phase became randomly variable. The results agree with the previous cytological observations of fixed embryonic cell populations in various animals, which showed that statistically calculated average lengths of cell cycle phases are expressed as linear functions of cell cycle time which increase as embryos develop (Brugal 1971; Weintraub et al . 1971; Kato 1975; Dan et al .…”
Section: Discussionsupporting
confidence: 92%
“…We observed that lengths of S and M phases, as well as the length of the G1 phase later, increase after MBT and can be expressed as linear functions of cell cycle time, although in our observations lengths of the G2 phase became randomly variable. The results agree with the previous cytological observations of fixed embryonic cell populations in various animals, which showed that statistically calculated average lengths of cell cycle phases are expressed as linear functions of cell cycle time which increase as embryos develop (Brugal 1971; Weintraub et al . 1971; Kato 1975; Dan et al .…”
Section: Discussionsupporting
confidence: 92%
“…2) and the cell cycle time here measured are fairly close (12 hr and 9 hr, respectively), it is likely that most of the erythroid cells are in cycle during day 1 .5-3 .5 . A lengthening of cell cycle times in the primitive cell series as the cells become more mature has been described in ovo (Weintraub, et al ., 1971) . Cell cycle time by thymidine ,3H pulse using de-embryonated chick blastoderms, six to nine somites .…”
Section: Cell Cycle Time Of Erythroid Cells In Early Culturementioning
confidence: 94%
“…Rat kangaroo (PtK.>) cells were maintained in F15 medium with 10% fetal calf serum and the same antibiotics used for the mouse cell lines. Erythroid cells were obtained from chick embryos as described elsewhere Weintraub et al, 1971). The first 24 h are designated day 0, 24-48 h as day 1, etc.…”
Section: ¡Materials and Methodsmentioning
confidence: 99%